COST EFFICIENCY OF RICE FARMING IN INDONESIA: STOCHASTIC FRONTIER APPROACH - Reynaldo Angga Siagian; Widyono Soetjipto (Socio-Economics/Agribusiness Department, 2020)
The main objectives of the study are to estimate the farm specific cost efficiency of rice production in Indonesia using Cost Frontier model and to identify and measure the impacts of different factors associated with cost efficiency of rice farmers. The study employed farm level cross sectional data for the years 2010 and 2016. Cost of Irrigation, Fertilizer and labor were found to contribute significantly in the cost efficiency of rice farmers. The average cost efficiency of rice production in 2016 is 83 percent, this result is more higher than 2010. This indicates a good potential for increasing rice output by 17 percent with the existing technology. The model claims that smaller land, more plot in the land, three time crop planting a year, and diversification significantly contribute to cost effeciency in farm production.